Comparison between the outcomes of combined phaco/trabeculectomy by cataract incision site - Tous, Horacio M.; Nevárez, Juan (Puerto Rico Health Sciences Journal, 2007)
Purpose: To analyze and compare the main outcomes of two techniques of combined surgery; mitomycin enhanced trabeculectomy combined with phacoemulsification and intraocular lens implantation through a single incision versus a two incisions approach. Patients and Methods: The authors retrospectively reviewed one surgeon’s consecutive 395 combined phacoemulsification/trabeculectomy surgeries. Patients were divided into two groups, those who underwent phacoemulsification and intraocular lens implantation through one incision (Phaco 1) and the other through two incisions (Phaco 2), both combined with trabeculectomy. Analysis of postoperative visual acuity, intraocular pressure, number of glaucoma medications, postoperative adverse events and additional procedures required, was done. Minimum follow-up was 12 months with an average of 49.2 months. Results: There was a significant difference (p = 0.0237) between the groups in terms of visual acuity improvement rate. By the end of the follow up period, both techniques were equally effective in reducing IOPs by an average of 8.1 mmHg. Postoperative pressure spikes occurred in 9% versus 11% (p = 0.6838) of the eyes. No significant difference (63% Phaco 1 versus 69% Phaco 2, p = 0.3230) between the two groups in terms of glaucoma medication reduction was found. There was no significant difference (p = 0.1181), in the total postoperative complications between the two groups (60% Phaco 1 vs. 51% Phaco 2), as well as in the total number of eyes which required further interventions (60% versus 68%, p = 0.2223). Conclusion: Combined phacoemulsification/ trabeculectomy using either a single or a two site approach, are equally effective in treating glaucoma patients with cataracts.